Utilizing E-Commerce to Maximize Shariah Banking Contracts in Indonesia - Muhammad Ady Mahfuzh; Oman Fathurohman SW; Dira Arum Cahyanudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The current development of Islamic banking consistently shows positive, ranging from assets, equity or market share which currently play a major role in maintaining the domestic economy. The aim of research to see the role optimality of e-Commerce in increasing market share of the Islamic banking from contracts products in Indonesia. The development of Islamic banking, cannot be separated from the banking system in Indonesia called this system is “dual banking system,” where conventional banks are allowed to open sharia business units that operate in the realm of banking. The role of Islamic banking in maintaining regional economic stability is increasingly strategic in realizing an increasingly balanced economic structure. By utilizing internet-based technology, the Islamic banking industry is expected to optimize its products in expanding market share that can be accessed easily and practically for everyone.